Risk sources, agility strategy and company performance among manufacturing small and medium enterprises in Malaysia (Global Business Management Review (GBMR), 2022)
Small and Medium Enterprise (SME), with its significant contribution to a country’s economy is gaining a corresponding interest from the research community. However, SMEs face numerous risks that could affect their performance resulting in its inability to rise to its full potential. Thus, this paper seeks to study the effect of risk sources (innovation and technology adoption risk, infrastructure risk and legal and regulation environment risk) towards company performance while introducing agility strategy in improving performance. Data was collected through a survey to Malaysian SME manufacturing companies yielding a response from 152 companies. Data were analysed using PLS-SEM. Findings indicate that innovation and technology adoption risk and legal and regulation environment risk have a significant effect on company performance. Meanwhile, the introduction of agility strategy does indicate a role in improvement of company’s performance in handling these risk sources. It would seem that agility strategy plays an effective role in mitigating risks therefore improving SME’s performance, contributing to knowledge of effective mitigating strategies in the field of risk management in supply chain for SMEs.